Quality of coffee drink from fruits submitted to different post-harvest management practices - Favarin, José Laércio; Villela, André Luis Gnaccarini; Moraes, Maria Heloisa Duarte; Chamma, Helena Maria Carmignani Pescarin; Costa, José Dias; Dourado-Neto, Durval (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the quality of the coffee drink from fruits with different postharvest management practices, considering the initial plant disease infection and during the coffee fruit exposition period. The following basic assumptions were defined: the harvested grain from the plant has higher coffee fruit drink potential quality, and the quality can be evaluated using fast tests and sensorial analysis. Eight treatments were established based on the post-harvest management with and without benzalcone chloride disinfection. The coffee fruit drink quality was not affected by the post-harvest management, including the treatment with 12 hours grain exposition after harvest. The fast tests were not correlated with the coffee drink sensorial analysis. The electric conductivity test was more sensitive than the potassium lixiviation test, and the grain modification occurred after six hours of fruit exposition. The efficiency of fruit superficial disinfection was verified during the first hour after immersion, decreasing the number of fruits infected by Cladosporium sp., Penicillum sp. and Alternaria sp.